Pengetahuan Bahaya Rokok dan Tindakan Merokok pada Remaja di SMA Negeri 1 GalisPamekasan - Friandany Natakusuma Shabir; Abu Bakar; Sukma Randani Ismono (Universitas Airlangga, 2019)
Introduction: Smoking among adolescents had became a global epidemic in Indonesia that lead to disability, illness and death. Smoking prevalence rate among teenagers over the years continued to rise even to the level of concern. The aimes of this research was to analyze the relationship between knowledge of smoking dangers and the act of smoking in adolescents.Methods: This research used a cross sectional design.Sampling technique was used a simple random sampling and the result obtained 218 respondents through May 2012. The sample was student from X, XI science and XI social grades. The data were collected by using quetitionaires and were analyzed by using Spearman Rho with level of significance of p<0,05.Result: The result showed that 58% of respondents had a high level of knowledge, and 66% of respondents were never smoke. Based on the result spearman rho analyzes, there was a relationship between smoking dangers and the act of smoking in adolescents with significant relationshipp=0.025 and level of significant level was p<0.05.Discussion: It can be concluded that a good knowledge about smoking dangers cause adolescence doesn’t smoke. Suggestion for further research, all of the school staffs could contribute to increase the knowledge of the student about the smoking dangers so smoking amongstudents can be minimized.